Enhanced photocatalytic degradation of bisphenol A by Co-doped BiOCl nanosheets under visible light irradiation - Wang, Chu-Ya; Zhang, Ying-Jie; Wang, Wei-Kang; Pei, Dan-Ni; Huang, Gui-Xiang; Chen, Jie-Jie; Zhang, Xing; Yu, Han-Qing (Applied catalysis. B, Environmental, 2018)
[Display omitted] •Co-doped BiOCl nanosheets were synthesized using a simple hydrothermal method.•Co doping expanded the light absorption region and enhanced the charge separation.•Co-BiOCl nanosheets exhibited a drastically enhanced visible-light photoreactivity.•Mechanism for the photocatalytic bisphenol A degradation was elucidated in depth. Bismuth oxychloride (BiOCl) is a typical UV-light-sensitive photocatalyst with a unique layered structure, but exhibits no response towards visible light. This is a main limitation for its practical applications in photocatalytic degradation of pollutants. Among various methods to expand the light absorption region, doping modification is an efficient approach because it can tailor the band structure by forming a doping energy level without changing the layered structure substantially. In this case, the static electric field in the BiOCl crystal can be retained. Since cobalt (Co) exhibits good electrochemical properties, it is an ideal element for doping modification to expand the light absorption region and enhance the charge separation efficiency of BiOCl. In this work, Co-doped BiOCl nanosheets were prepared using a simple hydrothermal route. The doped Co expanded the light absorption region and enhanced the charge separation efficiency by forming a doping energy level in the band gap of BiOCl. As a result, the Co-BiOCl nanosheets exhibited an outstanding photocatalytic performance in degrading bisphenol A (BPA) under visible light irradiation with a degradation rate of 3.5 times higher than that of BiOCl. On the basis of the experimental results and density functional theory calculations, the mechanism of visible-light-driven catalytic BPA degradation by the Co-BiOCl nanosheets was elucidated. Therefore, the feasibility of Co-doping modification for BiOCl was confirmed, and a novel and efficient strategy was provided for the design and synthesis of high-performance photocatalysts.